2021
DOI: 10.3389/fmolb.2021.698182
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Phosphorylation Modulates the Self-Association of a Variably Modified Histone H3 Peptide

Abstract: Protein phosphorylation is a key regulatory mechanism in eukaryotic cells. In the intrinsically disordered histone tails, phosphorylation is often a part of combinatorial post-translational modifications and an integral part of the “histone code” that regulates gene expression. Here, we study the association between two histone H3 tail peptides modified to different degrees, using fully atomistic molecular dynamics simulations. Assuming that the initial conformations are either α-helical or fully extended, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have demonstrated that besides the abundance of the synthesized proteins, posttranslational modification (PTM) of the stress-related signaling proteins is particularly important to dynamically regulate signaling in response to invasion patterns originating from the pathogen ( Liu et al., 2019 ). Protein phosphorylation is one of the most thoroughly studied PTM and has been estimated to affect about 30% of total protein in plants ( Papamokos et al., 2021 ). For example, OsCERK1 functions in blast disease resistance by interacting with OsRLCK185 and transducing pathogen-associated molecular patterns immune signals into phosphorylation events to activate the MAPK Cascade ( Wang C. et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that besides the abundance of the synthesized proteins, posttranslational modification (PTM) of the stress-related signaling proteins is particularly important to dynamically regulate signaling in response to invasion patterns originating from the pathogen ( Liu et al., 2019 ). Protein phosphorylation is one of the most thoroughly studied PTM and has been estimated to affect about 30% of total protein in plants ( Papamokos et al., 2021 ). For example, OsCERK1 functions in blast disease resistance by interacting with OsRLCK185 and transducing pathogen-associated molecular patterns immune signals into phosphorylation events to activate the MAPK Cascade ( Wang C. et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that seminal peptides appear to have a role in sperm motility and thereby fertility [ 42 , 43 ]. Protein conformational changes, including protein/peptide aggregation, are often triggered by protein phosphorylation [ 44 , 45 ]. Protein phosphorylation plays a pivotal role in regulating biological processes, such as signal transduction and metabolic regulation, by changing protein conformation, activity, and interaction [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have suggested that the PHD finger of ING proteins can recognize the histone H3 tail with varying affinities depending on the methylation status of the K4 ( Champagne & Kutateladze, 2009 ; Soliman & Riabowol, 2007 ; Peña et al, 2006 ) as well as unmodified or various modifications like acetylation and phosphorylation ( Li & Li, 2012 ; Musselman & Kutateladze, 2011 ; Papamokos et al, 2021 ). The binding site of the PHD finger grips the K4 of the histone H3 tail while the R2 is coordinated in a neighboring pocket.…”
Section: Discussionmentioning
confidence: 99%